2017
DOI: 10.5194/acp-2017-961
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving Mobile Platform Gaussian-Derived Emission Estimates Using Hierarchical Sampling and Large Eddy Simulation

Abstract: Abstract. Mobile laboratory measurements provide information on the distribution of CH4 emissions from point sources such as oil and gas wells, but uncertainties are poorly constrained or justified. Sources of uncertainty and bias in ground-based Gaussian derived emissions estimates from a mobile platform were analyzed in a combined field and modeling study. In a field campaign where 1009 natural gas sites in Pennsylvania were sampled, a hierarchical measurement strategy was implemented with increasing complex… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…We used a point-source Gaussian Dispersion Model (GDM) (Bosanquet and Pearson 1936, Sutton 1953, Pasquill 1974, Stern 1976, De Visscher 2013 to estimate CH 4 emission rates. Other transect-based mobile dispersion studies (Rella et al 2015, Yacovitch et al 2015, Caulton et al 2017 often integrate observed concentration enhancements across the entire width of the plume. The integration method is suitable so long as certain conditions can be satisfied, such as the emission source height being within range of the sampling inlet height, signal to noise from the background is sufficient to fully resolve the plume edges, and the transect is perpendicular downwind of the plume.…”
Section: Methodsmentioning
confidence: 99%
“…We used a point-source Gaussian Dispersion Model (GDM) (Bosanquet and Pearson 1936, Sutton 1953, Pasquill 1974, Stern 1976, De Visscher 2013 to estimate CH 4 emission rates. Other transect-based mobile dispersion studies (Rella et al 2015, Yacovitch et al 2015, Caulton et al 2017 often integrate observed concentration enhancements across the entire width of the plume. The integration method is suitable so long as certain conditions can be satisfied, such as the emission source height being within range of the sampling inlet height, signal to noise from the background is sufficient to fully resolve the plume edges, and the transect is perpendicular downwind of the plume.…”
Section: Methodsmentioning
confidence: 99%
“…These are discussed in detail in SM-S3. Previous ground based mobile dispersion studies have recorded uncertainty estimates ranging from 50-350% (Caulton et al, 2017). To quantify methodological uncertainty in this study, we conducted a series of controlled release experiments at the Carbon Management Canada Research Institutes Field Research Station near Brooks, AB, described further in SM-S3.2.…”
Section: D) Uncertaintymentioning
confidence: 99%
“…Plume dispersion applications feed wind measurements paired with gaseous concentrations from mobile measurement platforms into gaussian dispersion models to locate emitting infrastructure, estimate source emission rates, and quantify emitted volumes of methane in oil and gas developments (Atherton et al, 2017;Caulton et al, 2017). In the gaussian dispersion model, emission rate scales linearly with wind speed.…”
Section: Field Resultsmentioning
confidence: 99%
“…Mobile surveying studies using trucks or sport utility vehicles (Atherton et al, 2017;Jackson et al, 2014;Phillips et al, 2013;Rella et al, 2015;Zazzeri et al, 2015) with anemometer placements above the vehicle are vulnerable to flow bias, and should use flow compensations to account for wind bias from the shape of the vehicle. Transect-based studies with anemometers placed atop sport utility vehicles (Caulton et al, 2017), should also apply flow compensations, although some transect-based studies using mobile laboratories (Roscioli et al, 2015;Yacovitch et al, 2015) with anemometers placed on a boom ahead of and above the vehicle are much more resilient to bias from the flow of the vehicle. Similarly, studies quantifying emissions in which the vehicle stops to obtain wind measurements (Brantley et al, 2014) and the anemometer is placed ahead of and above the vehicle, are unlikely to require compensations for the vehicle's flow field.…”
Section: Field Resultsmentioning
confidence: 99%